AB0796 Clinical picture of anti-jo-1 positive anti-synthetase syndrome at presentation and during follow-up. (23rd January 2014) - Scorletti, E.; Cavagna, L.; Caporali, R.; Fusetti, C.; Boffini, N.; Montecucco, C.
Abstract : Background: Anti-synthetase syndrome (AS) is a connective tissue disease characterized by myositis, arthritis, interstitial lung disease (ILD) and the presence of anti-synthetase antibodies, mostly anti-Jo-1. Patients with an incomplete form of AS have been described; however it is not known whether and when these patients will develop a full-blown clinical picture during the course of the disease Objectives: To evaluate whether and how the clinical spectrum of patients with a diagnosis of incomplete AS changes during follow-up Methods: All patients with anti-Jo-1 positive AS followed at our Department from 1991 were retrospectively evaluated for clinical features at the time of diagnosis and during follow-up. All patients had been regularly followed at our department. Two patients died during follow-up (after 57 and 106 months), whereas two patients were lost to follow-up after 92 and 118 months. All the remaining patients had their last visit after August 2011. Anti-Jo-1 positivity was confirmed in stored frozen sera from all patients using EliA Jo-1 fluoroenzyme-immunoassay (Phadia 250 automatic instrumentation, Phadia GmbH, Freiburg, Germany) Results: For the purpose of this study, 18 patients (5 males/13 females) were analyzed. Median age at onset was 52.5 years (IQR 45-69) and median follow-up was 75 months (IQR 38-95). At the time of diagnosis, 8 patients (44%) had a complete form. The remaining 10 patients had an incomplete form; 5 had isolated arthritis, 3 arthritis and ILD, 1 arthritis and myositis and 1 had isolated ILD. At the last follow-up visit, a complete form of the disease was present in 14 patients (78%). Five patients with isolated arthritis developed both myositis and ILD within 3 months to 13 years, and 1 out of 3 patients with arthritis and ILD developed myositis after 2 years. Finally, the patient with isolated ILD developed arthritis after 21 months Conclusions: Clinical presentation of anti-Jo-1 AS is quite variable as only 44% of patients had a complete form at onset. In particular, myositis was present in 50% of the patients diagnosed at our department and ILD in 67%. A long and careful follow-up is mandatory in patients with incomplete syndrome as myositis and ILD may occur even very late during the course of the disease Disclosure of Interest: None Declared